Effectiveness of the XBB.1.5 COVID-19 Vaccines Against SARS-CoV-2 Hospitalisation Among Adults Aged ≥ 65 Years During the BA.2.86/JN.1 Predominant Period, VEBIS Hospital Study, Europe, November 2023 to May 2024 - Antunes, Liliana; Rojas-Castro, Madelyn; Lozano, Marcos; Martínez-Baz, Iván; Leroux-Roels, Isabel; Borg, Maria-Louise; Oroszi, Beatrix; Fitzgerald, Margaret; Dürrwald, Ralf; Jancoriene, Ligita; Machado, Ausenda; Petrović, Goranka; et al. (Influenza and other respiratory viruses, 2025)
We estimated the effectiveness of the adapted monovalent XBB.1.5 COVID-19 vaccines against PCR-confirmed SARS-CoV-2 hospitalisation during the BA.2.86/JN.1 lineage-predominant period using a multicentre test-negative case-control study in Europe. We included older adults (≥ 65 years) hospitalised with severe acute respiratory infection from November 2023 to May 2024. Vaccine effectiveness was 46% at 14-59 days and 34% at 60-119 days, with no effect thereafter. The XBB.1.5 COVID-19 vaccines conferred protection against BA.2.86 lineage hospitalisation in the first 4 months post-vaccination.
Keywords: vakcinace; účinnost vakcíny; Humans; Case-Control Studies; studie případů a kontrol; Vaccination; Female; Aged; senioři; lidé; Europe; hospitalizace; COVID-19 Vaccines; COVID-19; ženské pohlaví; vakcíny proti COVID-19; Hospitalization; Male; Aged, 80 and over; senioři nad 80 let; SARS-CoV-2; mužské pohlaví; Evropa; Vaccine Efficacy